The role of the autonomic nervous system in Tourette Syndrome - Hawksley, Jack; Cavanna, Andrea E.; Nagai, Yoko (Frontiers in Neuroscience, 2015)
Tourette Syndrome (TS) is a neurodevelopmental disorder, consisting of multiple involuntary movements (motor tics) and one or more vocal (phonic) tics. It affects up to one percent of children worldwide, of whom about one third continue to experience symptoms into adulthood. The central neural mechanisms of tic generation are not clearly understood, however recent neuroimaging investigations suggest impaired cortico-striato-thalamo-cortical activity during motor control. In the current manuscript, we will tackle the relatively under-investigated role of the peripheral autonomic nervous system, and its central influences, on tic activity. There is emerging evidence that both sympathetic and parasympathetic nervous activity influences tic expression. Pharmacological treatments which act on sympathetic tone are often helpful: for example, Clonidine (an alpha-2 adrenoreceptor agonist) is often used as first choice medication for treating TS in children due to its good tolerability profile and potential usefulness for co-morbid attention-deficit and hyperactivity disorder. Clonidine suppresses sympathetic activity, reducing the triggering of motor tics. A general elevation of sympathetic tone is reported in patients with TS compared to healthy people, however this observation may reflect transient responses coupled to tic activity. Thus the presence of autonomic impairments in patients with TS remains unclear. Effect of autonomic afferent input to cortico-striato-thalamo-cortical circuit will be discussed schematically. We additionally review how TS is affected by modulation of central autonomic control through biofeedback and Vagus Nerve Stimulation (VNS). Biofeedback training can enable a patient to gain voluntary control over covert physiological responses by making these responses explicit. Electrodermal biofeedback training to elicit a reduction in sympathetic tone has a demonstrated association with reduced tic frequency. VNS, achieved through an implanted device